2022
DOI: 10.1186/s12967-022-03258-1
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of PDGFRA and MUC family gene mutations in diffuse hemispheric glioma, H3 G34-mutant: a glimmer of hope?

Abstract: Background Diffuse hemispheric glioma H3 G34-mutant (G34-DHG) is a new type of pediatric-type diffuse high-grade glioma in the fifth edition of the WHO Classification of Tumors of the Central Nervous System. The current treatment for G34-DHG involves a combination of surgery and conventional radiotherapy or chemotherapy; however, the therapeutic efficacy of this approach is not satisfactory. In recent years, molecular targeted therapy and immunotherapy have achieved significant benefits in a va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“… 5 It has been found that alterations in the PDGFRA gene might indicate poor prognosis and potentially represent a therapeutic target for patients with G34-DHG. 14 One study exploring biomarkers of survival in 15 patients with G34-DHG demonstrated that patients exhibiting PDGFRA mutations tended to exhibit shorter OS, while those that had MUC16 alterations might have a more favorable survival, although patient numbers were limited and neither result was statistically significant. 14 Our study did not assess outcomes based on tumor mutational burden where hypermutation has been reported in some patients with G34-DHG at the time of relapse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 It has been found that alterations in the PDGFRA gene might indicate poor prognosis and potentially represent a therapeutic target for patients with G34-DHG. 14 One study exploring biomarkers of survival in 15 patients with G34-DHG demonstrated that patients exhibiting PDGFRA mutations tended to exhibit shorter OS, while those that had MUC16 alterations might have a more favorable survival, although patient numbers were limited and neither result was statistically significant. 14 Our study did not assess outcomes based on tumor mutational burden where hypermutation has been reported in some patients with G34-DHG at the time of relapse.…”
Section: Discussionmentioning
confidence: 99%
“… 14 One study exploring biomarkers of survival in 15 patients with G34-DHG demonstrated that patients exhibiting PDGFRA mutations tended to exhibit shorter OS, while those that had MUC16 alterations might have a more favorable survival, although patient numbers were limited and neither result was statistically significant. 14 Our study did not assess outcomes based on tumor mutational burden where hypermutation has been reported in some patients with G34-DHG at the time of relapse. 8 Tumor mutational burden might also be an important biomarker for future assessment on outcome and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular investigations may be also useful to stratify the prognosis in a more precise manner. In fact, better prognosis is associated with the presence of MGMT promoter methylation and MUC gene mutations, while a worse prognosis is associated with PDGFRA mutations and the amplification of oncogenes, such as PDGFRA , EGFR , CDK4, and MDM2 ( Korshunov et al, 2016 ; Hu et al, 2022 ; Vuong et al, 2022 ). Furthermore, the demonstration of alterations in PDGFRA and MUC genes might be potentially useful to open up new therapeutic options for these patients ( Lucas et al, 2021 ; Hu et al, 2022 ).…”
Section: Pediatric-type Diffuse High-grade Gliomasmentioning
confidence: 99%
“…It has been proposed via in vivo murine models that H3G34R/V mutations arise from GSX2+-expressing interneuron progenitor cells and that the mutations delay neuronal differentiation and increase PDGFRA overexpression, ultimately linking PDGFRA aberration to gliomagenesis [ 19 ]. While some studies indicate that the presence of mutations in PDGRA or EGFR may confer prognosis better than others [ 16 , 17 ], further investigation is required.…”
Section: Discussionmentioning
confidence: 99%